Advanced economy inflation: the role of global factors - Irena Mikolajun; David Lodge (European Central Bank (ECB), 2016)
A number of studies document the prominent role of global factors in domestic inflation developments (e.g. Borio and Filardo, 2007; Ciccarelli and Mojon, 2010). In this paper we investigate global dimensions of advanced economy inflation. We estimate open-economy Phillips curves for 19 advanced economies. We include backwardand forward-looking survey measures of inflation expectations and augment Phillips curves with global factors including global economic slack, global inflation and commodity prices. Our results provide little support for the existence of direct effects of global economic slack on domestic inflation. Moreover, the results suggest that the importance of global inflation in forecasting domestic inflation has its roots solely in its ability to capture slow-moving trends in inflation rates. In the Phillips curve context much the same role is performed by domestic forward-looking inflation expectations. With the exception of commodity prices therefore our results reveal little reason to include global factors into traditional reduced form Phillips curves.
Keywords: E31; E32; E37; 330; advanced economies; forecasting; global economic slack; global inflation; inflation; Phillips curve